PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE TERHADAP HASIL BELAJAR MAHASISWA PADA MATA KULIAH PENGANTAR DASAR MATEMATIKA-FKIP UMSU - Ismail Saleh Nasution (MES: Journal of Mathematics Education and Science, 2019)
Abstract. The purpose of this study is to find out the effect of cooperative learning type Think Pair Share on student learning outcomes in basic mathematics introductory courses at the FKIP PGMS UMSU Study Program. This study was a quasi-experimental study, using the one group pretest posttes only model, using one class as the study sample. The research instrument used in this study was a test / quiz in the form of 23 objective / multiple choice questions about set material and relationships contained in the basic mathematics introductory course. Based on the data obtained from the research results, there is an increase in the quality of learning in two stages, namely before the application of the Think Pair Share learning model and after the application of the Think Pair Share learning model. It can be seen that the values obtained by students at the post-test stage are superior and than before the application of the Think Pair Share learning model. The research hypothesis testing is related to how much influence the application of Think Pair Share learning models to improving student learning outcomes is done through statistical tests / t test. The result, obtained Tcount = 3.64. Then compared with Ttaraf at df = n-1, df = 42-1 = 41. With a real level of α of 0.05 is 2.02, if the price of Tcount is compared to T(table). It turns out Tcount T(table) (3.64 2.02). This figure shows that the Think Pair Share learning model has a positive effect on the ability to understand the subject matter of Basic Mathematics Introduction for students of the FKIP UMSU PGSD Study Program.Keywords: Think Pair Share, Basic Introduction to Mathematics